Rare Case of Aspergillus ochraceus Osteomyelitis of Calcaneus Bone in a Patient with Diabetic Foot Ulcers - Farhang Babamahmoodi; Tahereh Shokohi; Fatemeh Ahangarkani; Mojtaba Nabili; Elham Afzalian Ashkezari; Sosan Alinezhad (Case Reports in Medicine)
Diabetes is the most common metabolic disease in humans. One of the major complications of the disease is foot ulcer that is prone to infection. The most common causes of infection which have been reported in these patients are bacteria and fungi such as Candida, Aspergillus, and Rhizopus species. We report one such rare case with calcaneal osteomyelitis caused by Aspergillus ochraceus in a patient with diabetic foot osteomyelitis. The case was a 68-year-old male with a history of type II diabetes for 2 years. The patient had two ulcers on the right heel bones for the past 6 months with no significant improvement. One of the most important predisposing factors to infectious diseases, especially opportunistic fungal infection, is diabetes mellitus. Aspergillus species can involve bony tissue through vascular system, direct infection, and trauma. Proper and early diagnosis and treatment of diabetic foot infection can reduce or prevent complications, such as osteomyelitis and amputation. The annual examination of feet for skin and nail lesion, sensation, anatomical changes, and vascular circulation can be useful for prevention and control of infection.